TAWHID: As a Basis for Science Development - Anwar, Abu; Yasin, Arbi; Yusra, Nelly; Mujtahid, Iqbal Miftakhul; Hardila, Dilva (Journal of Natural Science and Integration, 2023)
The development of science and technology is currently so rapid and has become an inevitable need. Religion through its noble books certainly has a lot of knowledge. For this reason, it is necessary to carry out scientific integration between science and Islam, in this case Al Qur’an and Hadith. However, there are pros and cons to this view. In accordance with the establishment of UIN Suska as an Islamic University that provides education based on Islamic values, the aim of this study is to support the integration of Islam in the science learning process so that it can increase our understanding of the concept of tawhid, not reverse. The research method developed was a literature review by collecting data from various sources, both books, journals, and scientific articles. The result of this study is a literature review of tawhid as a basis for the science development. Thereby, in this case, science goes hand in hand with Islamic understanding so that it can strengthen the faith and tawhid on mankind as signs of the Oneness and glory of Allah SWT.Keywords: Tawhid, Science, Knowledge, Islam